Changes in renal WT-1 expression preceding hypertension development - Mazzei, Luciana Jorgelina (2016)
Background: Hypertension is a public health problem with mostly unknown causes, and where strong hereditary genetic alterations have not been fully elucidated. However, the use of experimental models has provided valuable information. Recent evidences suggest that alterations in key nephrogenic factors, such as Wilms' tumor 1 transcription factor (WT-1), could contribute to the development of hypertension. The aim of this paper is to evaluate the expression of WT-1 and related genes in the nephrogenic process in connection with the development of hypertension as well as the corresponding anatomical and functional correlation. Methods: Male spontaneously hypertensive and control rats were evaluated weekly from birth until week 8 of life. Their blood pressure was taken weekly using the tail-cuff blood pressure system. Weekly, 5 rats per group were sacrificed with a lethal injection of pentobarbital, and their kidneys were removed, decapsulated and weighed. The serum was collected for measuring biochemical parameters. The results were assessed using one-way analysis of variance for comparisons between groups. Results: The relationship between renal weight/total body weights was established, without significantly different values. These data were compared with apoptosis, fibrosis, number and size of the glomeruli. The elevation of systolic blood pressure was significant since week 6. Biochemical values differed slightly. Histology showed a slight increase in deposits of collagen fibers since week 4. Additionally, in kidney cortices, the expression of WT-1, heat shock protein 70 (Hsp70) and vitamin D receptors (VDR) decreased since week 4. Finally, we demonstrated ultrastructural damage to mitochondria since week 4. Conclusions: Our results would suggest an unprecedented link, possibly a regulatory mechanism, between WT-1 on nephrogenic alteration processes and their relationship with hypertension. Moreover, and previous to the increase in blood pressure, we demonstrated low expressions of WT-1, VDR and Hsp70 in kidneys from neonatal SHRs. If so, this may suggest that deregulation in the expression of WT-1 and its impact on nephrogenesis induction could be crucial in understanding the development and maintenance of hypertension.